The Influence of Management Control System Implementation and Work Motivation on Employee Performance - Sultan Hidayattulloh; Gun Gunawan Rachman; Uswatun Hasanah (Business Management, 2026)
This study aims to analyze the effect This study aims to analyze the effect of management control system implementation and work motivation on employee performance at the West Java Provincial Plantation Office. The implementation of a management control system is a process of controlling organizational activities through strategic planning, performance measurement, risk evaluation, reporting and communication, monitoring and correction, as well as employee participation, while work motivation reflects the internal drive that influences employees’ enthusiasm and responsibility in carrying out their duties. Employee performance is measured based on work quality, work quantity, timeliness, effectiveness, independence, and work commitment. This study used a quantitative method with descriptive and verificative approaches by distributing questionnaires to 42 respondents. The data analysis technique used was Structural Equation Modeling-Partial Least Square (SEM-PLS) to examine the effect of independent variables on the dependent variable. The results showed that management control system implementation and work motivation had a positive and significant effect on employee performance. These findings indicate that improving management control system implementation and work motivation can support employee performance improvement in public sector organizations.